Preparation method and application of lightweight heat-insulation cement aerogel material

By preparing lightweight thermally insulated cement aerogel materials, the problems of low insulation efficiency and high density of traditional explosion-proof box insulation materials in high temperature environments are solved, and the comprehensive effects of efficient thermal insulation, lightweight, compressive strength and high temperature stability are achieved.

CN119912225AActive Publication Date: 2025-05-02JIANGSU SOBUTE NEW MATERIALS CO LTD +1

Patent Information

Application Number
CN202510136296.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-05-02
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

Traditional explosion-proof box insulation materials have low insulation efficiency, high density and insufficient non-flammable properties in high temperature and harsh environments, resulting in equipment overheating, equipment failure and explosion hazards, and the heavy weight affects the stability and safety of the equipment.

Method used

The preparation method of lightweight thermally insulated cement aerogel materials is adopted to prepare materials with high strength, lightweight, non-flammable and excellent thermal insulation properties by improving the water-gluing ratio, adding reinforcing fibers, using foaming agents and hydrophobic components, and combining frozen pore formation and directional freezing technology.

Benefits of technology

It realizes efficient heat insulation of explosion-proof boxes, reduces density, improves compressive strength and high temperature stability, avoids equipment overheating and explosion hazards, and at the same time reduces the weight of the equipment and improves the convenience of transportation and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912225A_ABST
    Figure CN119912225A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material engineering, in particular to a preparation method and application of a light heat insulation cement aerogel material.The preparation method comprises the following steps that an adhesive is taken and dissolved in water, and then the solution is cooled to the room temperature; adding a dispersing agent into the solution, then adding cement, uniformly stirring, adding a hydrophobic component, and uniformly stirring; reinforcing fibers are added and evenly stirred, and the reinforcing fibers are at least one of polymer fibers, carbon fibers and glass fibers; adding the foaming component, and uniformly stirring; pouring the solution into a mold, performing freezing pore-forming by using liquid nitrogen, and recovering to room temperature after the freezing pore-forming is finished; and then drying to obtain the cement aerogel material after the drying is finished. The cement aerogel material prepared by the invention has excellent characteristics of high strength, light weight, non-flammability and the like, is used for a buffer layer of an explosion-proof tank, and can integrally improve the performance of the explosion-proof tank.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material engineering technology, and more specifically, to a preparation method and application of a lightweight thermal insulation cement aerogel material. Background Art

[0002] In the complex system of modern industry, explosion-proof boxes occupy a pivotal position and are widely distributed in many key industries such as petrochemicals, coal mining, pharmaceuticals, and electricity. The petrochemical field is full of a large number of flammable gases and liquids, such as gasoline vapor in refineries and various flammable and explosive chemicals in chemical workshops; coal mines are always filled with extremely dangerous flammable gases such as gas; pharmaceutical factories are often accompanied by volatile organic solvents, and the flammable mixed gas formed after their volatilization is everywhere; the power system may also produce a combustible dust environment due to dust accumulation. In such a high-risk environment, the explosion-proof box is like a solid safety barrier, which properly protects the internal electrical equipment, precision instruments, etc., and avoids the contact of dangerous factors such as electric sparks and arcs caused by internal electrical component failures or high temperatures caused by current overload with external flammable and explosive substances, thereby preventing the occurrence of catastrophic explosion accidents. At the same time, it can also resist shock waves and high-temperature radiation to the maximum extent when an explosion occurs outside, ensuring the relative safety of the equipment in the box.

[0003] However, with the rapid advancement of industrial production technology and the increasingly stringent standards for safe production, explosion-proof boxes are facing unprecedented performance challenges, and thermal insulation performance is the core concern. In many actual industrial scenarios, explosion-proof boxes are often placed in high-temperature and harsh environments. For example, in the core production area of ​​an oil refinery, the ambient temperature around various high-temperature reaction devices remains high all year round, and the continuous high-temperature thermal radiation is like an invisible killer, constantly threatening the normal operation of the explosion-proof box and its internal equipment. For another example, when an unexpected disaster such as a fire strikes, the explosion-proof box instantly becomes the direct target of high-temperature flames and must withstand the high temperature of external flames of up to thousands of degrees Celsius in a short period of time.

[0004] Looking back at traditional explosion-proof box insulation materials, such as common glass fiber wool and rock wool, they have played a certain role in insulation in the past, but under today's high standards, their defects are exposed. The insulation efficiency of these traditional materials is relatively low, and it is difficult to build a solid and reliable thermal resistance line under long-term high temperature invasion. Taking a chemical production workshop as an example, under a continuous high-temperature operating environment, the internal temperature of the explosion-proof box using traditional insulation materials will gradually rise over time, and may eventually exceed the temperature threshold allowed for the normal operation of the equipment in the box, causing the equipment to malfunction due to overheating, and then trigger a series of chain reactions, such as electrical short circuits and sparks, which is undoubtedly a major hidden danger of causing explosions in explosion-proof areas.

[0005] In addition, the physical properties of traditional insulation materials also bring many inconveniences to the application of explosion-proof boxes. Their density is generally high, which significantly increases the overall weight of the explosion-proof box. In some special application scenarios, such as offshore oil drilling platforms, where space is limited and the stability and weight control requirements of the equipment are extremely high, overweight explosion-proof boxes will affect the overall structural balance and safety of the platform; in aerial work equipment, heavy explosion-proof boxes will increase the load of the equipment, reduce operating efficiency and increase safety risks.

[0006] What is more serious is that when traditional insulation materials encounter extreme high temperatures or direct flame impact, they often undergo a series of adverse physical or chemical changes. They may shrink and deform, resulting in gaps in the insulation layer, allowing a large amount of heat to flow in; or they may melt, causing the insulation function to be lost instantly; or they may even release harmful gases, which will not only corrode the equipment in the box and reduce its service life, but also mix with external combustible materials when an explosion occurs, further increasing the power and scope of the explosion.

[0007] In summary, in the face of increasingly complex industrial production environments and rising safety demands, as well as the booming development of new materials technology, the full development of new explosion-proof box insulation materials with excellent insulation efficiency, light weight, excellent high-temperature stability and green environmental protection has become an important research topic that needs to be tackled in the field of industrial safety. This is of immeasurable significance for ensuring the stability, safety and sustainable development of industrial production. Summary of the invention

[0008] The present application provides a preparation method and application of a lightweight heat-insulating cement aerogel material. The cement aerogel material prepared in the present application has excellent properties such as high strength, light weight and non-flammability, and is used for the buffer layer of an explosion-proof box, which can improve the overall performance of the explosion-proof box.

[0009] In the first aspect, the present application provides a method for preparing a lightweight thermal insulation cement aerogel material, which adopts the following technical solution: A method for preparing a lightweight thermal insulation cement aerogel material comprises the following steps: S1: Dissolve the adhesive in water, the mass ratio of adhesive to water is (0.4~0.6):(14~18), and then cool the solution to room temperature; S2: Add dispersant to the solution of S1, then add cement and stir evenly. The mass ratio of cement to water is (1~1.25):(14~18); S3: Add hydrophobic components and stir evenly; S4: adding reinforcing fiber and stirring evenly, wherein the reinforcing fiber is at least one of polymer fiber, carbon fiber and glass fiber, the length of the reinforcing fiber is 10-20 mm, the diameter is 10-15 μm, and the mass ratio of the reinforcing fiber to cement is 0.2:(1-1.25); S5: Add foaming components and stir evenly; S6: Pour the solution of S5 into the mold, use liquid nitrogen to freeze and create holes, and then return to room temperature after completion; S7: Put the mold and the product after the freezing and pore forming in S6 into an oven for drying. After drying, a cement aerogel material is obtained.

[0010] Furthermore, the adhesive includes at least one of agarose, sodium alginate, chitosan, hyaluronic acid, polyacrylic acid derivatives, sodium polyacrylate, polyethylene glycol, polyacrylamide, and polyurethane.

[0011] Furthermore, in step S2, cement is added in at least two times.

[0012] Furthermore, the dispersant includes at least one of a sulfonate water reducer, a naphthalene water reducer and a polycarboxylic acid water reducer, and the mass ratio of the dispersant to cement is 0.03:(1-1.25).

[0013] Furthermore, the cement is sulphoaluminate cement or a mixture of sulphoaluminate cement and silicate cement.

[0014] Furthermore, the hydrophobic component includes at least one of trimethoxysilane and triethoxysilane, and the mass ratio of the hydrophobic component to cement is 0.12: (1-1.25).

[0015] Furthermore, the foaming component is one of hydrogen peroxide, sodium bicarbonate, ammonium carbonate, and ammonium bicarbonate, and the mass ratio of the foaming component to cement is 0.5: (1-1.25).

[0016] Furthermore, in step S6, the freezing pore making is directional freezing, the freezing temperature is -120~-180℃, and the time is 30-60min.

[0017] Furthermore, in step S7, the drying temperature is 50-80°C.

[0018] In a second aspect, the present application provides an application of a lightweight thermal insulation cement aerogel material, using the following technical solution: An application of a lightweight heat-insulating cement aerogel material, wherein the cement aerogel material is used as a heat-insulating material for an explosion-proof box.

[0019] In summary, this application has the following beneficial effects: The present application adopts fast-hardening cement as the skeleton to ensure the overall strength of the material, so that its structure will not be easily destroyed when subjected to external force impact. In addition, cement is chemically inert, and its corrosion resistance, combustion resistance, and penetration resistance make it a good protective material. However, the water-cement ratio of general cement materials is too low. Although it can ensure strength, the density is high and cannot meet the requirements of light weight. Therefore, the present application adopts a higher water-cement ratio, which can achieve the light weight requirements of aerogel materials. At the same time, in order to avoid the problem of strength reduction caused by too high a water-cement ratio, the present application also adds reinforcing fibers.

[0020] In terms of lightweight requirements, the present application improves the water-to-binder ratio of the material while combining pore-making with foaming agent and directional freezing technology to increase the porosity of the material and reduce its total mass. Compared with conventional explosion-proof boxes that are generally heavy and difficult to carry, the present application can make the explosion-proof box easy to carry and transport.

[0021] In terms of strength requirements, the present application adds reinforcing fibers, but the use of reinforcing fibers often results in uneven dispersion, which reduces material performance and affects the foaming of the aerogel itself in the present application. Therefore, the present application optimizes the size parameters of the reinforcing fibers themselves and adds adhesives to assist in the uniform dispersion of the reinforcing fibers. This does not affect the pore formation of the foaming components and the directional freezing pore formation, making the pore structure of the present application uniform and orderly, which greatly reduces the density while further improving the strength of the material.

[0022] Finally, the preparation method of the present application has significant low cost, simplicity and environmental protection. The raw materials used are widely available and easy to obtain, which reduces the production cost. At the same time, the entire preparation process is safe and environmentally friendly, in line with the concept of sustainable development. The preparation process is simple and clear, easy to control, and is conducive to large-scale industrial production, thereby promoting the widespread application of this technology in the field of construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Sample picture obtained in Example 1.

[0024] Figure 2 Compressive strength curve of the sample obtained in Example 1.

[0025] Figure 3 Microstructure diagram obtained in Example 1. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0027] The present application first provides a method for preparing a lightweight thermal insulation cement aerogel material, comprising the following steps: S1: Dissolve the adhesive in water, the mass ratio of adhesive to water is (0.4~0.6):(14~18), and then cool the solution to room temperature; S2: Add dispersant to the solution of S1, and then add cement. The cement is added at least twice and stirred evenly. The mass ratio of cement to water is (1~1.25): (14~18); S3: Add hydrophobic components and stir evenly; S4: Add reinforcing fiber and stir evenly, wherein the reinforcing fiber is at least one of polymer fiber, carbon fiber and glass fiber, the length of the reinforcing fiber is 10-20 mm, the diameter is 10-15 μm, and the mass ratio of the reinforcing fiber to cement is 0.2: (1-1.25); the polymer fiber can be one of polypropylene fiber, polyethylene fiber, polystyrene fiber, polyester fiber, polyamide fiber, polyvinyl alcohol fiber, and the polymer molecular weight is 300-500.

[0028] S5: Add foaming components and stir evenly; S6: Pour the solution of S5 into the mold and use liquid nitrogen to freeze and form holes. The freezing and forming holes are directional freezing. The freezing temperature is -120~-180℃ and the time is 30-60min. After the freezing, the temperature is restored to room temperature. S7: Put the mold and the product after the freezing and pore forming in S6 into an oven for drying at 50-80° C. After drying, a cement aerogel material is obtained.

[0029] Furthermore, the adhesive includes at least one of agarose, sodium alginate, chitosan, hyaluronic acid, polyacrylic acid derivatives, sodium polyacrylate, polyethylene glycol, polyacrylamide, and polyurethane.

[0030] Furthermore, the dispersant includes at least one of a sulfonate-based water reducer, a naphthalene-based water reducer, and a polycarboxylic acid water reducer, and the mass ratio of the dispersant to the cement is 0.03:(1-1.25).

[0031] Furthermore, the cement is sulphoaluminate cement or a mixture of sulphoaluminate cement and silicate cement. Specifically, in the embodiment of the present application, the sulphoaluminate cement is sulphoaluminate white cement Polar Bear 62.5, and the silicate cement is silicate (Helin 62.5) cement. Furthermore, the hydrophobic component includes at least one of trimethoxysilane and triethoxysilane, and the mass ratio of the hydrophobic component to cement is 0.12: (1-1.25).

[0032] Furthermore, the foaming component is one of hydrogen peroxide, sodium bicarbonate, ammonium carbonate, and ammonium bicarbonate, and the mass ratio of the foaming component to cement is 0.5: (1~1.25).

[0033] The cement aerogel material prepared above can be used as a heat insulation material for explosion-proof boxes.

[0034] The following is an explanation through specific examples.

[0035] Example 1 S1. Weigh 0.48 parts of polyethylene glycol 400 and dissolve it in 14 parts of water, and return the solution to room temperature.

[0036] S2. Add 0.03 parts of Subot polycarboxylate water reducer 801, and then slowly add 0.5 parts of sulphoaluminate white cement Polar Bear 62.5, stirring time is 30min, stirring speed is 500 r / min. Then slowly add 0.5 parts of sulphoaluminate white cement and continue stirring.

[0037] S3. Add 0.12 parts of hydrophobic component methyltrimethylsilane and stir for 30 minutes.

[0038] S4. Add 0.2 parts of glass fiber and stir for 30 minutes.

[0039] S5. Add 0.5 parts of hydrogen peroxide as the foaming component and stir for 1 minute.

[0040] S6. Immediately pour the solution into the prepared mold and freeze it with liquid nitrogen at -150°C for 45 minutes. After freezing, thaw and return to room temperature.

[0041] S7. After returning to room temperature, place the entire mold into an oven for drying. The oven temperature is set to 80°. After drying, a cement aerogel material sample S1 is obtained.

[0042] Example 2 S1. Weigh 0.48 parts of sodium polyacrylate (molecular weight 2100) and dissolve it in 14 parts of water, and return the solution to room temperature.

[0043] S2. Add 0.03 parts of polycarboxylate water-reducing agent Subot 801, and then slowly add 0.625 parts of cement, which is a mixture of sulphoaluminate cement and silicate (Helin 62.5) cement in a mass ratio of 1:1. Stir for 30 minutes at a stirring speed of 500r / min. Then slowly add 0.625 parts of the above cement and continue stirring.

[0044] S3. Add 0.12 parts of hydrophobic component and stir for 30 minutes.

[0045] S4. Add 0.2 parts of glass fiber and stir for 30 minutes.

[0046] S5. Add 0.5 parts of hydrogen peroxide as the foaming component and stir for 1 minute. S6. Immediately pour the solution into the prepared mold and use liquid nitrogen to freeze and create holes at -150°C for 60 minutes. After freezing, thaw and return to room temperature.

[0047] S7. After returning to room temperature, the mold is placed in an oven for drying, and the oven temperature is set to 80°. After drying, a cement aerogel material sample S2 is obtained.

[0048] Example 3

[0049] S1. Weigh 0.48 parts of sodium alginate and dissolve it in 14 parts of water, and return the solution to room temperature.

[0050] S2. Add 0.03 parts of naphthalene-based water reducer Subot (SBT-JM-A), then slowly add 0.625 parts of sulphoaluminate cement, stirring for 30 minutes at a stirring speed of ~500 r / min. Then slowly add 0.625 parts of sulphoaluminate cement and continue stirring.

[0051] S3. Add 0.12 parts of hydrophobic component methyltrimethylsilane and stir for 30 minutes.

[0052] S4. Add 0.2 parts of glass fiber and stir for 30 minutes.

[0053] S5. Add 0.5 parts of hydrogen peroxide as the foaming component and stir for 1 minute.

[0054] S6. Immediately pour the solution into the prepared mold and freeze it with liquid nitrogen at -150°C for 30 minutes. After freezing, thaw and return to room temperature.

[0055] S7, after returning to room temperature, put the entire mold into an oven for drying, and set the oven temperature to 80°. After drying, the cement aerogel material sample S3 can be obtained.

[0056] Example 4 S1. Weigh 0.48 parts of polyacrylamide (molecular weight 5 million) and dissolve it in 14 parts of water. Return the solution to room temperature.

[0057] S2. Add 0.03 parts of naphthalene-based water reducer Subot (SBT-JM-A), then slowly add 0.625 parts of sulphoaluminate cement, stirring for 30 minutes at a stirring speed of ~500 r / min. Then slowly add 0.625 parts of sulphoaluminate cement and continue stirring.

[0058] S3. Add 0.12 parts of hydrophobic component methyltrimethylsilane and stir for 30 minutes.

[0059] S4. Add 0.2 parts of glass fiber and stir for 30 minutes.

[0060] S5. Add 0.5 parts of hydrogen peroxide as the foaming component and stir for 1 minute.

[0061] S6. Immediately pour the solution into the prepared mold and freeze it with liquid nitrogen at -150°C for 45 minutes. After freezing, thaw and return to room temperature.

[0062] S7, after returning to room temperature, put the entire mold into an oven for drying, and set the oven temperature to 80°. After drying, the cement aerogel material sample S4 can be obtained.

[0063] Example 5 S1. Weigh 0.6 parts of polyethylene glycol 400 and dissolve it in 14 parts of water, and return the solution to room temperature.

[0064] S2. Add 0.03 parts of naphthalene-based water reducer Subot (SBT-JM-A), then slowly add 0.5 parts of sulphoaluminate cement, stirring for 30 minutes at a stirring speed of ~500 r / min. Then slowly add 0.5 parts of sulphoaluminate cement and continue stirring.

[0065] S3. Add 0.12 parts of hydrophobic component methyltrimethylsilane and stir for 30 minutes.

[0066] S4. Add 0.2 parts of glass fiber and stir for 30 minutes.

[0067] S5. Add 0.5 parts of hydrogen peroxide as the foaming component and stir for 1 minute. S6. Immediately pour the solution into the prepared mold and use liquid nitrogen to freeze and create holes at -150°C for 45 minutes. After freezing, thaw and return to room temperature.

[0068] S7, after returning to room temperature, put the entire mold into an oven for drying, and set the oven temperature to 80°. After drying, the cement aerogel material sample S5 can be obtained.

[0069] Example 6 S1. Weigh 0.6 parts of polyethylene glycol 400 and dissolve it in 18 parts of water, and return the solution to room temperature.

[0070] S2. Add 0.03 parts of naphthalene-based water reducer Subot (SBT-JM-A), then slowly add 0.5 parts of sulphoaluminate cement, stirring for 30 minutes at a stirring speed of ~500 r / min. Then slowly add 0.5 parts of sulphoaluminate cement and continue stirring.

[0071] S3. Add 0.12 parts of hydrophobic component methyltrimethylsilane and stir for 30 minutes.

[0072] S4. Add 0.2 parts of glass fiber and stir for 30 minutes.

[0073] S5. Add 0.5 parts of hydrogen peroxide as the foaming component and stir for 1 minute.

[0074] S6. Immediately pour the solution into the prepared mold and freeze it with liquid nitrogen at -150°C for 45 minutes. After freezing, thaw and return to room temperature.

[0075] S7, after returning to room temperature, put the entire mold into an oven for drying, and set the oven temperature to 80°. After drying, the cement aerogel material sample S6 can be obtained.

[0076] Example 7

[0077] S1. Weigh 0.48 parts of polyethylene glycol 400 and dissolve it in 14 parts of water, and return the solution to room temperature.

[0078] S2. Add 0.03 parts of Subot polycarboxylate water reducer 801, and then slowly add 0.5 parts of sulphoaluminate white cement Polar Bear 62.5, stirring time is 30min, stirring speed is 500 r / min. Then slowly add 0.5 parts of sulphoaluminate white cement and continue stirring.

[0079] S3. Add 0.12 parts of hydrophobic component methyltrimethylsilane and stir for 30 minutes.

[0080] S4. Add 0.2 parts of carbon fiber and stir for 30 minutes.

[0081] S5. Add 0.5 parts of hydrogen peroxide as the foaming component and stir for 1 minute.

[0082] S6. Immediately pour the solution into the prepared mold and freeze it with liquid nitrogen at -180°C for 30 minutes. After freezing, thaw and return to room temperature.

[0083] S7. After returning to room temperature, the entire mold is placed in an oven for drying. The oven temperature is set to 80°. After drying, a cement aerogel material sample S7 is obtained.

[0084] Example 8 S1. Weigh 0.48 parts of polyethylene glycol 400 and dissolve it in 14 parts of water, and return the solution to room temperature.

[0085] S2. Add 0.03 parts of Subot polycarboxylate water reducer 801, and then slowly add 0.5 parts of sulphoaluminate white cement Polar Bear 62.5, stirring time is 30min, stirring speed is 500 r / min. Then slowly add 0.5 parts of sulphoaluminate white cement and continue stirring.

[0086] S3. Add 0.12 parts of hydrophobic component methyltrimethylsilane and stir for 30 minutes.

[0087] S4. Add 0.2 parts of polypropylene fiber with a molecular weight of 300-500 and stir for 30 minutes.

[0088] S5. Add 0.5 parts of hydrogen peroxide as the foaming component and stir for 1 minute.

[0089] S6. Immediately pour the solution into the prepared mold and freeze it with liquid nitrogen at -120°C for 60 minutes. After freezing, thaw and return to room temperature.

[0090] S7. After returning to room temperature, place the entire mold into an oven for drying. The oven temperature is set to 80°. After drying, a cement aerogel material sample S8 is obtained.

[0091] Comparative Example The difference between Comparative Example 1 and Example 1 is that no polyethylene glycol is added.

[0092] The difference between Comparative Example 2 and Example 1 is that no reinforcing fiber is added.

[0093] The difference between Comparative Example 3 and Example 1 is that silicate cement is used instead of sulphoaluminate cement.

[0094] The difference between Comparative Example 4 and Example 1 is that liquid nitrogen is used for freezing pore formation, the freezing temperature is -80°C and the freezing time is 30 minutes.

[0095] The difference between Comparative Example 5 and Example 1 is that the amount of polyethylene glycol used is 0.25 parts.

[0096] The difference between Comparative Example 6 and Example 1 is that the amount of polyethylene glycol used is 0.65 parts The difference between Comparative Example 7 and Example 1 is that the amount of reinforcing fiber used is 0.25 parts.

[0097] The difference between Comparative Example 8 and Example 1 is that the length of the reinforcing fiber is 25-35 mm and the diameter is 10-15 μm.

[0098] The difference between Comparative Example 9 and Example 1 is that the length of the reinforcing fiber is 1-10 mm and the diameter is 1-10 μm.

[0099] The difference between Comparative Example 10 and Example 1 is that the amount of water used is 10 parts.

[0100] Performance Testing The performance of the samples obtained in the embodiments and comparative examples was tested, and the test results are shown in Table 1. The compressive strength test method refers to GB / T 34336-2017, and the thermal conductivity refers to GB / T 10295. The control sample is a commercially available porous calcium silicate board HCS-20 from Hebei Huajun Insulation Materials Co., Ltd.

[0101] Table 1 Performance test results Compressive strength(MPa) Thermal conductivity (W / (m・K)) <![CDATA[Density (kg / m 3 )]]> Comparison Example 0.54 0.063 220 Example 1 0.86 0.038 92 Example 2 0.87 0.043 106 Example 3 0.93 0.042 118 Example 4 0.91 0.041 112 Example 5 0.72 0.039 97 Example 6 0.87 0.037 89 Example 7 0.88 0.039 94 Example 8 0.85 0.038 90 Comparative Example 1 - - - Comparative Example 2 0.58 0.038 89 Comparative Example 3 0.28 0.091 185 Comparative Example 4 0.36 0.067 166 Comparative Example 5 0.68 0.047 118 Comparative Example 6 0.67 0.038 93 Comparative Example 7 0.63 0.044 105 Comparative Example 8 0.65 0.046 102 Comparative Example 9 0.59 0.041 97 Comparative Example 10 0.92 0.051 132 Comparative analysis of the performance of the embodiment and the control example shows that the thermal insulation material obtained in the present application has a more excellent thermal insulation performance, and while its density is reduced, it has good compressive strength, which makes the sample have great advantages as a lightweight explosion-proof box insulation filling material. Figure 1~Figure 3 As can be seen from the product-related performance diagram of Example 1, the pore structure of the product of Example 1 is uniform and orderly, which greatly reduces the density while improving the strength of the material.

[0102] Further, the performance of comparative example 1 is analyzed to find that comparative example 1 lacks a bonding component and cannot be formed, and is a powder after freeze drying. Further analysis of the performance of comparative example 5 shows that the amount of adhesive used in comparative example 5 is reduced, and the performance of each phase thereof is deteriorated, indicating that the use of the adhesive in the present application not only plays a bonding role, but also helps to enhance the dispersion of the fibers and the formation of an ordered pore structure. However, the adhesive in comparative example 6 is further increased, and the final performance is still not good, indicating that the amount of adhesive used must be reasonably controlled to achieve a balance between the performance of each phase, and thus the product has excellent comprehensive performance.

[0103] Further, the performance of comparative example 2 is analyzed and it is found that comparative example 2 lacks reinforcing fibers, and while the density and thermal conductivity are reduced, the compressive strength is significantly reduced. In addition, combined with the performance of comparative example 7, it can be seen that the use of reinforcing fibers cannot be too much, otherwise it will have a greater negative impact on the product. In addition, combined with the performance of comparative examples 8 and 9, it can be seen that the size of the reinforcing fibers has a certain influence on the product, because the reinforcing fibers can not only improve the strength of the product, but the use of reinforcing fibers will also have a certain influence on the pore structure of the product. The length of the reinforcing fibers used in this application is 10~20mm and the diameter is 10~15μm, which can better play a role in the system of this application and improve product performance.

[0104] Further, the performance of comparative example 3 was analyzed. Comparative example 3 used silicate cement, and the strength was not supported, resulting in shrinkage during the drying process of the sample. Combined with the performance of comparative example 10, it was found that the control of the water-cement ratio is very important for the performance of the product.

[0105] Further, analysis of the performance of Comparative Example 4 revealed that the freezing temperature of Comparative Example 4 was low, the freezing speed was slow, the freezing was non-directional, the strength of the sample was greatly reduced after drying, and the shrinkage was severe.

[0106] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a lightweight thermal insulation cement aerogel material, characterized in that: The following steps are involved: S1: Dissolve the adhesive in water, the mass ratio of adhesive to water is (0.4~0.6):(14~18), and then cool the solution to room temperature; S2: Add dispersant to the solution of S1, then add cement and stir evenly. The mass ratio of cement to water is (1~1.25):(14~18); S3: Add hydrophobic components and stir evenly; S4: adding reinforcing fiber and stirring evenly, wherein the reinforcing fiber is at least one of polymer fiber, carbon fiber and glass fiber, the length of the reinforcing fiber is 10-20 mm, the diameter is 10-15 μm, and the mass ratio of the reinforcing fiber to cement is 0.2:(1-1.25); S5: Add foaming components and stir evenly; S6: Pour the solution of S5 into the mold, use liquid nitrogen to freeze and create holes, and then return to room temperature after completion; S7: Put the mold and the product after the freezing and pore forming in S6 into an oven for drying. After drying, a cement aerogel material is obtained.

2. The method for preparing a lightweight thermal insulation cement aerogel material according to claim 1, characterized in that: The adhesive includes at least one of agarose, sodium alginate, chitosan, hyaluronic acid, polyacrylic acid derivatives, sodium polyacrylate, polyethylene glycol, polyacrylamide, and polyurethane.

3. The method for preparing a lightweight thermal insulation cement aerogel material according to claim 1, characterized in that: In step S2, cement is added at least twice.

4. The method for preparing a lightweight thermal insulation cement aerogel material according to claim 1, characterized in that: The dispersant includes at least one of a sulfonate water reducer, a naphthalene water reducer and a polycarboxylic acid water reducer. The mass ratio of the dispersant to cement is 0.03:(1-1.25).

5. The method for preparing a lightweight thermal insulation cement aerogel material according to claim 1, characterized in that: The cement is sulphoaluminate cement or a mixture of sulphoaluminate cement and silicate cement.

6. The method for preparing a lightweight thermal insulation cement aerogel material according to claim 1, characterized in that: The hydrophobic component includes at least one of trimethoxysilane and triethoxysilane, and the mass ratio of the hydrophobic component to cement is 0.12: (1-1.25).

7. The method for preparing a lightweight thermal insulation cement aerogel material according to claim 1, characterized in that: The foaming component is one of hydrogen peroxide, sodium bicarbonate, ammonium carbonate and ammonium bicarbonate, and the mass ratio of the foaming component to cement is 0.5:(1-1.25).

8. The method for preparing a lightweight thermal insulation cement aerogel material according to claim 1, characterized in that: In step S6, the freezing pore making is directional freezing, the freezing temperature is -120~-180℃, and the time is 30-60min.

9. The method for preparing a lightweight thermal insulation cement aerogel material according to claim 1, characterized in that: In step S7, the drying temperature is 50-80°C.

10. An application of a lightweight thermal insulation cement aerogel material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The cement aerogel material is used as a heat insulation material for explosion-proof boxes.

Citation Information

Patent Citations

  • Foam cement insulation material for exterior wall and preparation method thereof

    CN102942380A

  • Preparation method of directional porous special cement

    CN103739306A

  • Method for preparing gradient directional porous cement based on two-phase pore former system freezing molding technology

    CN106892674A

  • Mortar composition

    JP1985215587A

  • Method of manufacturing lightweight foamed cement foam

    KR101985722B1

Cited By

  • High-performance magnesium phosphate cement material based on multi-stage complexing-network construction coordinated regulation

    CN121225978A

  • A high-performance magnesium phosphate cement material based on multi-level complex-network construction and synergistic regulation

    CN121225978B

  • Cement-based aerogel material and preparation method thereof

    CN121292898A

  • A cement-based aerogel material and its preparation method

    CN121292898B

  • Fibrous ettringite, lightweight cement aerogel material for pipeline lining based on fibrous ettringite and preparation method of lightweight cement aerogel material

    CN121627038A